A Model for Sustainable Adoption of Solar Photovoltaic Technology in Tanzania - Raymond, J.; Kihedu, J. H.; Kimambo, C. Z. M. (Tanzania Journal of Engineering and Technology, 2022)
Solar photovoltaic (PV) technology has been used for several decades to meet the electric energy need of various communities in Tanzania, particularly in rural areas that face a supply gap, due to various reasons. This study builds on three previous projects that were implemented at different locations of the United Republic of Tanzania. These projects are the Sustainable Solar Market Packages 1 (SSMP 1) Project, which was implemented in Sumbawanga District; the Sida/MEM Solar Project, which was implemented in several regions of Tanzania Mainland and the UNDP/MEM Solar PV Project, which was implemented in Mwanza region. The aim was to develop a sustainable model for enhancement of the solar PV technology adoption in Tanzania. The model was developed based on the identified barriers that hinder the adoption of solar PV technology and adopted the best strategies from successful projects. Further, the drivers and activities were developed based on selected best strategies from successful projects. The identified barriers to the adoption of solar PV technology were grouped into five categories based on their significances. These include; limited access to finance (32%), weak enforcement of relevant policy and regulations (31%), technical capacity (18%), lack of awareness (9%) and other social drivers (10%). The analysis of information and data that was obtained from the project reports shows that there are prevailing challenges on awareness on solar PV technology and non-enforcement of quality standards. However, major barriers are on the high price of solar PV systems and lack of access to finance. A model for adoption of solar PV technology in Tanzania was developed and tested by validating it with a successfully implemented solar PV project in Tanzania. In the validation, thirteen (13) out of twenty-one (21) activities of the UNDP/MEM Solar PV Project demonstrated the moderate compliance with the model prescription by 62%. The UNDP/MEM Solar PV project developed a financing mechanism but it was not sustainable due to low application of sustainable adoptions strategies. Also, most of the strategies lacked some important drivers and activities due to financial constraints and technical know-how. The mechanism was not opening opportunities for new users to adopt the solar PV technology or maintain the existing ones. Moreover, stakeholders have not put in place the conducive conditions for existing projects to be sustainable. Recommended future interventions include application of the developed adoption model for Solar PV by using data from other solar PV projects for sensitivity analysis of identified barriers and best strategies. Keywords: Solar energy, photovoltaic, technology adoption, project model, and sustainable project.